Prevalence and correlates of multimorbidity among adults in border areas of the Central Highland Region of Vietnam, 2017. (27th May 2019) - Ba, Nguyen Van; Minh, Hoang Van; Quang, Le Bach; Chuyen, Nguyen Van; Ha, Bui Thi Thu; Dai, Tran Quoc; Duc, Duong Minh; Quynh, Nguyen Thuy; Khanh, Pham Gia
Introduction: The objectives of this study are to estimate the prevalence of multimorbidity (MM) among adults in the Central Highland Region (a poor region) of Vietnam in 2017 and to identify the sociodemographic correlates of these conditions. Methods: We used data from a cross-sectional study conducted in 2018 on health status among people in four provinces in the Central Highlands Region (Tay Nguyen) of Vietnam. A sample of 1680 adults (aged 15 years and older) were randomly selected for this study. Respondents were asked whether they had been told by a health worker that they had cancer, heart and circulatory conditions, chronic joint problems, chronic pulmonary diseases, chronic kidney problems, chronic digestive problems, psychological illness, diabetes, and/or other chronic conditions. Results: The prevalence of MM among the study participants was 16.4% (95% confidence interval (CI): 14.6%–18.2%). By looking at the 95% CIs, the differences in MM prevalence between the groups classified by gender, age, education, and occupation were not statistically significant. Only the difference in MM prevalence between farmers and government staff was statistically significant. Multivariate logistic analyses show education and occupations were shown to be significant correlates of MM. Conclusion: MMs were quite common among the adult populations in the study area, especially among people with lower socioeconomic status. Given the evidence, actions to reduce levels of MM in the setting are clearly urgent. The interventions should address all people in society, with focus on disadvantaged groups, like those with lower education and farmers.